Nonlinear optical susceptibilities in the diffusion modified AlxGa1–xN/GaN single quantum well. (May 2018) - Das, T.; Panda, S.; Panda, B.K.
Abstract: Under thermal treatment of the post growth AlGaN/GaN single quantum well, the diffusion of Al and Ga atoms across the interface is expected to form the diffusion modified quantum well with diffusion length as a quantitative parameter for diffusion. The modification of confining potential and position-dependent effective mass in the quantum well due to diffusion is calculated taking the Fick's law. The built-in electric field which arises from spontaneous and piezoelectric polarizations in the wurtzite structure is included in the effective mass equation. The electronic states are calculated from the effective mass equation using the finite difference method for several diffusion lengths. Since the effective well width decreases with increasing diffusion length, the energy levels increase with it. The intersubband energy spacing in the conduction band decreases with diffusion length due to built-in electric field and reduction of effective well width. The linear susceptibility for first-order and the nonlinear second-order and third-order susceptibilities are calculated using the compact density matrix approach taking only two levels. The calculated susceptibilities are red shifted with increase in diffusion lengths due to decrease in intersubband energy spacing. Highlights: Under thermal treatment, the as-grown AlGaN/GaN single quantum well modifies to diffusion modified well. The built-in electric field in the wurzite structure modifies the confining potential. The electronic states are evaluated by solving the effective mass equation for different diffusion lengths. The susceptibilities for different orders are calculated using the density matrix approach.. The susceptibilities get red shifted with increase in diffusion length due to decrease in intersubband energy spacing..